Regio- and stereoselective C-H functionalization of brassinosteroids - Hurski, Alaksiej L; Kukel, Aliaksandr G; Liubina, Aliaksandra I; Baradzenka, Aliona G; Straltsova, Darya; Demidchik, Vadim; Drašar, Pavel; Zhabinskii, Vladimir N; Khripach, Vladimir A (Steroids, 2019)
Late stage CH functionalization is a powerful tool for modification of natural compounds. Herein we report that the rhodium-catalyzed reaction of brassinosteroids with aryloxysulfonamides proceeds regio- and stereoselectively at C15 position. The derivative obtained from 24-epibrassinolide was easily transformed to the conjugate with a BODIPY dye bearing unaffected functional groups of the native brassinosteroid.
Keywords: stereoizomerie; sloučeniny boru; Stereoisomerism; brassinosteroidy; katalýza; rhodium; Boron Compounds; Rhodium; Brassinosteroids; Catalysis